RAJASTHAN’S POLITICS AND WOMEN’S LEADERSHIP - Pareek, Swati; Mishra, Charu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper refers to Rajasthan’s politics, which mainly assesses the proper representation given to women by political parties. In the concept of sustainable development, along with the economic upliftment of all classes, the ideology of women empowerment also got strength. In this sequence, various types of schemes and programs are being run by the Rajasthan government. The priority of the central and state governments has always been the development of women. The result of which can be seen that the governments have been successful in increasing the number of women voters. But the question arises that whether the political parties which bring schemes related to women’s upliftment also keep gender equality in representation. This research paper shows the representation of women in political parties through secondary data which is based on factual and qualitative levels. On the basis of the above-analyzed facts, the researcher sends many suggestions through this article which are necessary for the Indian political system.